5(8F)+4(9-F)+37=

Simple and best practice solution for 5(8F)+4(9-F)+37= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(8F)+4(9-F)+37= equation:


Simplifying
5(8F) + 4(9 + -1F) + 37 = 0

Remove parenthesis around (8F)
5 * 8F + 4(9 + -1F) + 37 = 0

Multiply 5 * 8
40F + 4(9 + -1F) + 37 = 0
40F + (9 * 4 + -1F * 4) + 37 = 0
40F + (36 + -4F) + 37 = 0

Reorder the terms:
36 + 37 + 40F + -4F = 0

Combine like terms: 36 + 37 = 73
73 + 40F + -4F = 0

Combine like terms: 40F + -4F = 36F
73 + 36F = 0

Solving
73 + 36F = 0

Solving for variable 'F'.

Move all terms containing F to the left, all other terms to the right.

Add '-73' to each side of the equation.
73 + -73 + 36F = 0 + -73

Combine like terms: 73 + -73 = 0
0 + 36F = 0 + -73
36F = 0 + -73

Combine like terms: 0 + -73 = -73
36F = -73

Divide each side by '36'.
F = -2.027777778

Simplifying
F = -2.027777778

See similar equations:

| 0.1x/x=0.56 | | f(x)=x^2+3x-88 | | n^2-27n+168=0 | | 12-6x+4-x=3+8x+13-11x | | z^2-14z=-11 | | 6+5x=-7x+78 | | -23-3m=-20 | | 1/x=0.079461 | | 6(2x+1)=6-13x | | 54x+2x=1 | | 5(x+3)=5x-2 | | -6(n+3)=-6n+3(n-12) | | 3s-5=16 | | 6(2x+11)=6-13x | | Ab+bc+abc= | | 12(m-12)=6(1+7m) | | 6-5+10= | | -6(k+11)=6(k-5) | | x^2+12x=324 | | 4(x+-2)=3(1.5+x) | | 32+32x=-4(-8x+1) | | 6/7s=-1/6 | | (7x+1)+(5x-1)=180 | | -89=-3(-3v+4)-5 | | (x+y)(a+b)=0 | | ax+bx+2=-8 | | 2/8=5/x | | 8(-5m-2)-6m=260 | | 0=-26t^2+44t+5 | | -7x+50=-2x+15 | | 8(5n-2)=-336 | | -4x/ |

Equations solver categories